THERMODYNAMIC PROPERTIES OF BINARY LIQUID MIXTURE OF TOLUENE WITH BENZENE - GOLAMARI SIVA REDDY,; MALLU MAHESWARA REDDY, (International Journal of Pharma and Bio Sciences, 2014)
The experimental densities and viscosities of Toluene with benzene at temperatures of 303.15, 308.15 and 313.15K were determined using a vibrating-tube density meter and Oswald Viscometer. From these data, excess molar volumes and viscosity deviations have been calculated. The computed quantities have been fitted to the respective models to derive the coefficients and estimate the standard error values. The results are discussed in terms of the molecular interactions.